2018
DOI: 10.3390/met8030170
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characteristics and m23c6 Precipitate Behavior of the Course-Grained Heat-Affected Zone of T23 Steel without Post-Weld Heat Treatment

Abstract: The microstructural characteristics of a simulated heat-affected zone (HAZ) in SA213-T23 (2.25Cr-1.6W steel) used for boiler tubes employed in thermal power plants were investigated using nital, alkaline sodium picrate, and Murakami's etchants. In order to investigate the microstructure formation process of the HAZ in the welding process, simulated HAZ specimens were fabricated at intervals of 100 • C for peak temperatures between 950 and 1350 • C, and the microstructural features and precipitate behavior at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Therefore, fine secondary nbc carbides were precipitated within the grains, whereas m 23 c 6 carbides were formed mostly at the grain boundaries (Fig. 1(c)-(d)) [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, fine secondary nbc carbides were precipitated within the grains, whereas m 23 c 6 carbides were formed mostly at the grain boundaries (Fig. 1(c)-(d)) [10,11].…”
Section: Resultsmentioning
confidence: 99%
“…The M 23 C 6 intergranular precipitates inside the white band are concentrated in C, W, and Cr. It is considered that the depleted zone is formed around the M 23 C 6 precipitate because the M 23 C 6 carbide with high C, W, and Cr components precipitates at the grain boundary [24][25][26][27] when PWHT is carried out at 700 • C. According to a study by Lee et al, the black band in alkaline sodium picrate-etched CGHAZ is the segregated region of C, W, and Cr [19,20]. The black band at 700 • C is also a region where C, W, and Cr components are concentrated.…”
Section: Correlation Between Microstructure and Pwht Cracking Susceptmentioning
confidence: 99%
“…However, the research of Belde et al recently found that there is a microsegregation in the matrix where the alloying elements are not uniform, which can affect the mechanical properties and cause cracking in the course of the heat treatment [17,18]. According to Lee et al, the M 23 C 6 precipitate of the base metal in 2.25Cr-1Mo-Ti steel partially dissolves in the thermal cycle of CGHAZ, and the microsegregation of C and Cr appears as a black stripe [19,20]. It is considered that such a microsegregation can affect the mechanical properties of PWHT due to phase transformation other than the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the depleted zone is formed around the M23C6 precipitate because the M23C6 carbide with high C, W and Cr components precipitates at the grain boundary [24][25][26][27] when PWHT is carried out at 700℃. According to a study by Lee et al, the black band in alkaline sodium picrate etched CGHAZ is the segregated region of C, W, and Cr [19,20]. The black band at 700℃ is also a region where C, W, and Cr components are concentrated.…”
Section: Correlation Between Microstructure and Pwht Cracking Susceptmentioning
confidence: 99%
“…However, research of M. Belde et al recently found that there is a microsegregation in the matrix where the alloying elements are not uniform, which can affect the mechanical properties and cause cracking in the course of the heat treatment [17,18]. According to Lee et al, the M23C6 precipitate of the base metal in 2.25Cr-1Mo-Ti steel partially dissolves in the thermal cycle of CGHAZ, and the microsegregation of C and Cr appears as a black stripe [19,20]. It is considered that such a microsegregation can affect the mechanical properties of PWHT due to phase transformation other than the matrix.…”
Section: Introductionmentioning
confidence: 99%